1970
DOI: 10.1104/pp.45.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates Of Photosynthesis in Acetabularia mediterranie Chloroplasts

Abstract: The chloroplast fraction isolated from Acetabularia mediterranie was exposed to 14CO2 as NaH'4C03 in light and darkness, and soluble radioactive compounds were analyzed at frequent intervals. The behavior of Calvin cycle intermediates on the chloroplasts isolated from 2 to 3 g of cells, about 2 cm long, each preparation containing 600 to 750 j,g of total chorophyll (1). The chloroplasts were suspended in 5 ml of the A medium described earlier (6), except that the pH was reduced to 7.2 in order to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
6
1
Order By: Relevance
“…to detect any appreciable utilization of added amino acids, and recently synthesized amino acids seem to be used preferentially for protein synthesis Our results do not contradict previous studies (8,11) where it was reported that Acetabula, ia chloroplasts utilize 14C-amino acids. These authors were able to detect the incorporation of 20 ng of total amino acid per mg of protein in the sample (Goffeau, personal communication).…”
Section: Utilization Of Added Amino Acidscontrasting
confidence: 52%
See 4 more Smart Citations
“…to detect any appreciable utilization of added amino acids, and recently synthesized amino acids seem to be used preferentially for protein synthesis Our results do not contradict previous studies (8,11) where it was reported that Acetabula, ia chloroplasts utilize 14C-amino acids. These authors were able to detect the incorporation of 20 ng of total amino acid per mg of protein in the sample (Goffeau, personal communication).…”
Section: Utilization Of Added Amino Acidscontrasting
confidence: 52%
“…Serine, glyclne, alanine, and aspartic acid appear as free pools in the chloroplasts and are rapidly labeled from photosynthetic intermediates (8). The simplest explanation for their origin is by transamination or reducdve amination of the respective a-keto acids as typical in photosynthetic tissue.…”
Section: Pathways To Amino Acidsmentioning
confidence: 99%
See 3 more Smart Citations